SACST smart anthropomorphic contact surface technology. - Imin Kao (IEEE Robotics and automation magazine)
In this article, we present the ongoing research work of smart anthropomorphic contact surface technology (SACST) and applications in robotics and human-augmented systems. Integrating MEMS technology with contact theory and intelligent-control techniques, SACST can alter the behavior of contact surfaces based on robotics theories. To make SACST products more reliable and efficient, certain critical components are indispensable. For example, MEMS valves should be able to work under more resistant force and with less power consumption; the contact sensor should have higher and flexible resolution; and the actuation mechanism of the bladders should become more integrated, more flexible, and easier to control. Next-generation SACST technology will also integrate intelligent operation systems and control with actuators and sensors.